Experimental studies of the recombination processes in II-VI semiconductors (bulk crystals and epilayers) at variable excitation levels - Brodyn, M.S.; Shevel, S.G.; Tishchenko, V.V. (Condensed Matter Physics, 1999)
Low-temperature luminescence spectra under broad-scale variation of an excitation level Iexc are studied for ZnS/ZnSe single quantum wells (QW) and for CdS bulk crystals and epilayers. In the ﬁrst case, the manifestations turn out to be of the heterointerface inhomogeneity - i.e. ﬂuctuations of QW thickness. The position of the mobility edge for excitons localized by ﬂuctuations is determined. In the second case the effect of the increase of Iexc is systematically studied not only for excitonic but also for impurity-related edge luminescence. Contrary to the earlier and commonly assumed expectations, up to the highest Iexc close to damage threshold no saturation of edge luminescence intensity was observed in bulk CdS crystals, whereas in a few thick epilayers such saturation did occur. The suggested qualitative explanation takes into account diffusion (non-diffusive transport) of carriers beyond the excited near-surface layer.